Possibility of using natural cheeses for pizza production - G. M. Sviridenko; A. N. Shishkina; V. V. Kalabushkin (Пищевые системы, 2023)
The paper presents the results of studying sensory, physico-chemical, structural-mechanical (rheological) and biochemical indicators as well as functional properties of natural cheeses of various type groups for a possibility of using as a main raw material to produce pizza. Cheeses were produced in the research-and-development shop of the All-Russian Scientific Research Institute of Butter- and Cheesemaking (VNIIMS) and purchased in the retail chain. Sensory indicators (taste and odor, consistency, appearance) and functional properties (shreddability, meltability, blistering, free oil release, browning, stretchability) of cheeses from various groups were assessed by 100-point scale for assessing cheeses for pizza developed in VNIIMS. Shreddability was determined before baking by grinding a cheese sample chilled to a temperature of 4 ± 2 °C using a kitchen food grinder. Cheeses were baked at a temperature of 200 ± 5 °C for 12 min. Meltability was determined by changes in the cheese diameter after high-temperature treatment and stretchability by the “fork test”. It has been found that physico-chemical, structural-mechanical and biochemical indicators of cheeses used as a raw material affected sensory characteristics and functional properties of the final product after baking. The correlation between the fat content, protein mass fraction and active acidity of cheeses and functional properties such as meltability, free oil release, stretchability and shreddability was confirmed with statistical significance. The highest correlation was noted between shreddability, mass fraction of total protein and consistency (correlation coefficients were 0.74 and 0.76, respectively). However, none of the studied cheese types corresponded to the full extent to the targeted functional properties. To produce pizza, it is preferable to use cheeses with cheddaring and thermal-mechanical processing of cheese mass as well as unripened semihard cheeses with low temperature of the second heating that are molded from a layer, and semihard cheeses with high temperature of the second heating.